Book review: Sanjeev Jain and Alok Sarin (eds.), The Psychological Impact of the Partition of India. (June 2021) - Tanwar, Raghuvendra
Sanjeev Jain and Alok Sarin (eds.), The Psychological Impact of the Partition of India . New Delhi: SAGE Publications, 2018, 241 pp., ₹850, ISBN: 9789352806508.